Caulobacter and Novosphingobium in tumor tissues are associated with colorectal cancer outcomes - Zhou, Bin; Shi, Linli; Jin, Min; Cheng, Mingxia; Yu, Dandan; Zhao, Lei; Zhang, Jieying; Chang, Yu; Zhang, Tao; Liu, Hongli (Frontiers in Oncology, 2023)
Diversity and composition of the gut microbiome are associated with cancer patient outcomes including colorectal cancer (CRC). A growing number of evidence indicates that Fusobacterium nucleatum (Fn) in CRC tissue is associated with worse survival. However, few studies have further analyzed the differences in bacteria in tumor tissues of different patients depending on the survival time of CRC patients. Therefore, there is a need to further explore the bacterial differences in tumor tissues of patients with different prognoses and to identify key bacteria for analysis. Here, we sought to compare the differences in tumor microbiome between patients with long-term survival (LS) longer than 3 years or 4 and 5 years and patients with short-term survival (SS) in the present study cohort. We found that there were significant differences in tumor microbiome between the LS and SS and two bacteria—Caulobacter and Novosphingobium—that are present in all of the three groups. Furthermore, by analyzing bacteria in different clinical features, we also found that lower levels of microbiome (Caulobacter and Novosphingobium) have long-term survival and modulating microbiome in tumor tissue may provide an alternative way to predict the prognosis of CRC patients.